Arabic translation, cross-cultural adaptation, and validation of the Expectation for Treatment Scale (ETS) in patients with musculoskeletal disorders - Walid Mohamed; Michelle Hall; Jürgen Barth; Paul Hendrick (PLoS ONE, 2026)
Purpose To translate, culturally adapt the Expectation for Treatment Scale (ETS) into Arabic and evaluate its psychometric properties in patients with musculoskeletal disorders. Methods Following established guidelines, forward and backward translations were performed, each followed by a synthesis. Face validity of the Arabic ETS was evaluated by asking patients undergoing physiotherapy for musculoskeletal disorders to what extent the ETS items covered their outcome expectations. Internal consistency; test-retest reliability; measurement error; content validity; construct and structural validity, and floor and ceiling effects were assessed. Results The ETS was successfully translated and adapted according to the 24 patients’ feedback. 205 individuals completed the online questionnaire, and 36 completed it twice. The Arabic ETS demonstrated good internal consistency (α = 0.75), high test-retest reliability (ICC = 0.93 and κw = 0.75, 0.58, 0.55, 0.66, 0.70, for items one to five, respectively), low measurement error (SEM = 1.42, and SDC = 2.86), and acceptable content validity (0.78). Construct validity was supported (though not definitive) via known-group hypothesis testing (r = −0.331, p < .001) and exploratory factor analysis (χ²(66 = 218.73, p < 0.001). Differential item functioning confirmed the cross-cultural validity. There were minimal floor (0.5%) and ceiling (2%) effects. Conclusions The ETS was translated and adapted to Arabic culture. The assessed psychometric properties of the Arabic ETS support its reliable use in patients with musculoskeletal conditions.